Development of ecological strain-hardening cementitious composites incorporating high-volume ground-glass pozzolans. (30th March 2020) - Hisseine, Ousmane A.; Tagnit-Hamou, Arezki
Highlights: The use of glass powder (GP) increase the compactness and strength of SHCC. Enhancement in tensile strength exceeding 100% was obtained. Too high GP content adversely affects composite ductility. For optimum strength and ductility, GP content should be ≤40%. GP also enhances durability aspects (measured by the bulk electrical resistivity). Abstract: A novel strain-hardening cementitious composite (SHCC) incorporating high-volume ground-glass pozzolans (HVGP) has been developed by coupling particle packing optimization with micromechanical tailoring. For the former, the compressible packing density model was adopted, while for the latter, single-fiber pull-out and fracture mechanics tests were conducted to compile model input parameters. Ground-glass pozzolans also known as glass powder (GP) at up to 100% replacement of fly ash (FA) were attempted. The resulting HVGP-SHCC formulations have self-consolidating ability and exhibited up to 75 MPa compressive strength, 9–15 MPa flexural capacity, 3–6 MPa tensile strength, up to ≈3% tensile strain capacity, and a significantly improved durability (up to 80% enhancement in electrical bulk resistivity). Results reveal that the compactness-based formulation of HVGP-SHCC yielded composites exhibiting higher strength than conventional SHCC containing high-volume fly ash (HVFA) with similar water-to-binder ratio while demonstrating acceptable tensile strain capacity and far better durability aspects. Research outcomes shape a forward step in the development of greener high-performance construction materials necessary for sustainable and resilient concrete infrastructures.